How port community systems can contribute to port competitiveness: Developing a cost–benefit framework. (June 2016) - Carlan, Valentin; Sys, Christa; Vanelslander, Thierry
Abstract: The trend towards collaborative innovation in the maritime supply chain implies a good understanding of the actors and their roles, and an efficient exchange of information. A Port Community System (PCS) increases port efficiency by connecting the ICT systems of each of its members, thereby facilitating their communication. To verify whether this type of collaboration and its benefits actually materialize, an understanding of the costs and benefits of such PCS is required. This paper recognizes the inconsistency in the existing literature with respect to PCS costs and benefits quantification. Therefore, after an in-depth literature review, interviews with experts of PCS were carried out, a comprehensive framework to quantify the costs and benefits was developed. Next, a case study was drawn-up to develop a discussion regarding the costs and the extra benefits that port stakeholders incur when using a module of a PCS. The case analysis suggests that there is a positive cost–benefit balance for every stakeholder adhering to a PCS. By covering the development and operational costs of certain modules, PCS operators seek to increase the port competitiveness. This way, PCS users manage to gain higher net benefits and have a competitive advantage over other port stakeholders outside the community.